Penerapan Metode Statistical Process Control Pada Pengendalian Kualitas Single Part BS-62631-60M00 - Mohammad Vigan Alkharami; Jauhari Arifin; Ari Teguh Septiansyah (Peneliti.net, 2022)
The quality of a product is one of the most important factors in the industrial world in order to obtain high profits for the company. P, but the reality is that in the field, defective products are found in every production. So the company must find the cause of the defective product and find a solution by using SPC. The method used in this study uses statistical process control methods with data processing tools, namely flowcharts, check sheets, Pareto charts, control charts, and fishbones. The data needed in the study is the number of production and defective products in October 2020 - March 2021. The percentage of defective products experiencing the highest number of defects in December and March with a total defect of 30 with a percentage of 20%. The results found that in December and March experienced a high proportion of defects and exceeded the upper control limit (UCL). the control limit p with CL is 0.0059, the lower control limit is 0.00446, and the upper control limit is 0.00734. it was found that in December and March experienced a high proportion of defects and exceeded the upper control limit (UCL). several factors that affect product quality consisting of 5 (five) factors including: human factors, machines, method factors, raw material factors, and environmental factors